(untitled) (Journal of Fatima Jinnah Medical University, 2020)
ABSTRACT Background: In chronic hepatitis C infection, hepatic decompensation remained a contraindication to treatment for many years. The direct acting antiviral drugs have shown high treatment success even in decompensated liver disease. This study aims to assess the response and safety profile of Sofosbuvir and Daclatasvir in patients of decompensated cirrhosis with chronic hepatitis C. Patients and Methods: It was a prospective observational study conducted at Gastroenterology Department of Gujranwala Medical College/ DHQ teaching Hospital, Gujranwala from February 2016 to December 2017.Consecutive patients of hepatitis C with decompensated cirrhosis were enrolled in the study. Sofosbuvir 400mg and Daclatasvir 60mg was given to all patients without ribavirin for a period of 24 weeks. Sustained virologic was taken as primary end point. Results: A total of 140 patients were included in our study, 122 patients (87%) completed the study, 08 patients (5.7%) were lost to follow up, treatment discontinuation was seen in 06 patients (4.2%) & 04 patients (2.8%) died during the study. 110 patients (90.2%) achieved end treatment response (ETR), 12 patients (9.8%) remained treatment non-responder, 100 patients (82%) achieved sustained virological response (SVR12) and 10 patients (8%) had a relapse of HCV infection. Conclusion: Once daily oral Sofosbuvir plus Daclatasvir without Ribavirin achieved overall high rates of sustained virologic response in patients with chronic HCV having decompensated liver disease.